Measuring governance quality in Africa: how citizens’ lived experiences compare with aggregate indicators - Drennan, Dario Massimo; Drennan, Candace Grace (My University, 2020)
Abstract This research report deliberates on the measurement of the quality of governance in African countries through quantitative means. The complexities of governance were previously only assessed qualitatively. However, more recent attempts have been made to use quantitative approaches resulting in the formation of aggregate indicators of governance quality, such as the Worldwide Governance Indicator and Ibrahim Index of African Governance. The aim of this research report is to provide current data on a contemporary analysis of governance in African countries and to add to the field of measures of governance quality focusing on citizens’ lived experience. The specific research question addressed the measurement of governance quality in Africa and how citizens’ lived experiences compare with aggregate indicators. While aggregate indicators of governance quality include sources that capture pertinent citizens’ lived experiences, closer inspection showed that these sources are assigned very small weights in the calculations of the aggregate indicators. The key findings, using bivariate statistics, found that the correlation between the component measures of citizens’ experiences and the aggregate indicators were very weak, revealing that public opinion data on aggregate governance indicators had little impact.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts (Drama) to the Faculty of Humanities, University of the Witwatersrand, 2020